Preparation method of photo-thermal super-hydrophobic coating with excellent anti-icing / deicing performance in low-temperature and high-relative-humidity environment
By constructing a photothermal superhydrophobic coating with a three-stage micro/nano/nano structure under low temperature and high relative humidity environments, the problems of insufficient passive anti-icing performance and degraded active deicing performance in this environment are solved, and excellent anti-icing and deicing performance are achieved.
Patent Information
- Application Number
- CN202411914512.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing photothermal superhydrophobic coatings show problems such as insufficient passive anti-icing performance and sharp decline in active deicing performance under low temperature and high relative humidity environments.
Using raw materials with low thermal conductivity and simple spraying technology, a photothermal superhydrophobic coating with a three-stage micro/nano/nano structure is constructed on the surfaces of various substrates. The specific method includes growing photothermal Cu-MOF nanoparticles in situ on the surface of the fibrous clay mineral nanoparticles with low thermal conductivity, performing low thermal conductivity and introducing a low thermal conductivity binder, and forming a micron-scale binder/low-surface energy nanoparticle aggregate by spraying.
In low temperature and high relative humidity environments, the coating exhibits excellent photothermal properties and Cassie-Baxter state stability of the droplets on the coating surface, giving it excellent passive anti-icing/frosting and active deicing/defrosting properties. The low thermal conductivity further inhibits heat exchange between the substrate and water droplets, improving the passive anti-freeze/frost performance of the coating.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a photothermal super-hydrophobic coating, and in particular to a method for preparing a photothermal super-hydrophobic coating with excellent anti-icing / de-icing performance in a low temperature and high relative humidity environment, belonging to the technical field of super-hydrophobic anti-icing coating preparation. Background Art
[0002] Surface icing poses a serious threat to the safety and reliability of the operation of new energy facilities and causes huge economic losses. Traditional deicing methods, such as mechanical vibration and heat treatment, usually require a lot of manpower and material resources, and have low deicing efficiency. In recent years, researchers have gradually paid attention to passive anti-icing strategies, which are favored because of their high efficiency and low cost. To date, superhydrophobic coatings have become one of the most promising passive anti-icing solutions. Its excellent performance mainly comes from the high contact angle (>150°) and low rolling angle (<10°), which effectively reduces the contact area between solid and liquid, thereby delaying the formation of ice and reducing the adhesion strength of ice.
[0003] However, super-hydrophobic coatings can only delay ice formation, but cannot completely prevent ice formation. Therefore, photothermal super-hydrophobic coatings that combine passive anti-icing and active deicing functions are gradually becoming an effective anti-icing and deicing material. Patent CN109486269A prepares a photothermal super-hydrophobic coating with passive anti-icing and active deicing properties by spraying a low surface energy silicon micropowder / carbon nanotube dispersion on the surface of a substrate. Patent CN115260897B synthesizes polydimethylsiloxane microspheres with photothermal properties by emulsion polymerization and disperses them in a low surface energy silica nanoparticle dispersion, which is then sprayed onto a semi-dried fluorocarbon resin surface to prepare a photothermal super-hydrophobic passive anti-icing / active deicing coating.
[0004] Although significant progress has been made in the research of photothermal superhydrophobic passive anti-icing / active deicing coatings, the following problems still exist in practical applications: (1) In low temperature and high relative humidity environments, the passive anti-icing performance of the coating is insufficient. This is because: i) in this environment, it is difficult for droplets to maintain a stable Cassie-Baxter state on the coating surface, resulting in a sharp drop in anti-icing performance; ii) although superhydrophobic coatings can effectively reduce the contact area between the coating and the water droplets to inhibit heat exchange, it cannot be completely avoided, resulting in insufficient passive anti-icing performance of the coating. (2) Most photothermal superhydrophobic coatings show excellent performance under a light intensity of 1 sun, but the photothermal performance of the coating is insufficient under low temperature and high relative humidity environments, resulting in a sharp drop in its active deicing performance.
[0005] Therefore, the present invention, by adopting low thermal conductivity raw materials and simple spraying process, constructs a low thermal conductivity photothermal super hydrophobic coating with three-level micro / nano / nano structure on the surface of various substrates. Specific as follows: First, by in-situ growth of photothermal Cu-MOF nanoparticles on the surface of low thermal conductivity fibrous clay mineral nanomaterials, a two-level nano / nano structure of composite photothermal particles is constructed, which is then subjected to low surface energy modification and introduced into a low thermal conductivity binder, and a binder / low surface energy nanoparticle aggregate is formed by inducing the binder to undergo phase separation in a micrometer scale by a non-solvent, and finally a coating with three-level micro / nano / nano structure is constructed by spraying. The three-level micro / nano / nano structure of the coating not only gives the coating excellent photothermal performance under low temperature and high relative humidity environments, but also improves the Cassie-Baxter state stability of the droplets on the coating surface under this environment, so that it has excellent passive anti-icing / frosting and active deicing / defrosting performance under low temperature and high relative humidity environments. In addition, the low thermal conductivity of the coating further inhibits the heat exchange between the substrate and the water droplets, so that the passive anti-icing / frosting performance of the coating is further improved. The photothermal super-hydrophobic coating prepared by the present invention effectively solves the defects of the traditional (photothermal) super-hydrophobic anti-icing coating, which is of great significance for the practical application of the photothermal super-hydrophobic coating. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a photothermal super-hydrophobic coating with excellent anti-icing / de-icing performance in a low temperature and high relative humidity environment, which can effectively solve the problems existing in the practical application of current photothermal super-hydrophobic coatings.
[0007] 1. Preparation of photothermal super-hydrophobic coating The photothermal super-hydrophobic coating of the present invention is composed of a low thermal conductivity binder and low surface energy Cu-MOF@ fibrous composite nanoparticles, and the specific preparation method is as follows: (1) Preparation of Cu-MOF@fibrous composite nanoparticles: Dissolve copper nitrate and 2,3,6,7,10,11-hexahydroxytriphenylbenzene (HHTP) in a mixed solvent of N,N-dimethylformamide / water, stir for 3-8 min, then add low thermal conductivity fibrous clay mineral nanoparticles, continue stirring at 80-90 °C for 10-15 h, filter the resulting suspension, wash, dry, and grind to obtain Cu-MOF@fibrous composite nanoparticles with a two-level nano / nano structure; The concentration of the copper nitrate in the mixed solvent of N,N-dimethylformamide / water is 8-12 mg / mL; the concentration of the HHTP in the mixed solvent of N,N-dimethylformamide / water is 5-7 mg / mL; in the mixed solvent of N,N-dimethylformamide / water, the volume ratio of N,N-dimethylformamide to water is 1:10. The low thermal conductivity fibrous clay mineral nanoparticles are one of attapulgite, halloysite, and sepiolite; the concentration of the low thermal conductivity fibrous clay mineral nanoparticles in the mixed solvent of N,N-dimethylformamide / water is 15-40 mg / mL.
[0008] (2) Preparation of low surface energy Cu-MOF@fibrous composite nanoparticles: The Cu-MOF@fibrous composite nanoparticles prepared in (1) were dispersed in ethanol, stirred for 8-12 minutes, and then ultrasonically dispersed for 4-6 minutes. Ammonia water was then added and stirred for 4-6 minutes. Then, fluorosilane was added. The fluorosilane was hydrolyzed and condensed on the surface of the Cu-MOF@fibrous composite nanoparticles at room temperature. Finally, the obtained suspension was centrifuged, dried, and crushed to obtain low surface energy Cu-MOF@attapulgite composite nanoparticles. The concentration of the Cu-MOF@fibrous composite nanoparticles in the reaction system is 5-15 mg / mL; the volume ratio of the ethanol to the ammonia water is 49:1-40:10; the fluorosilane is one of perfluorooctyltriethoxysilane and perfluorodecyltriethoxysilane, and the mass ratio of the fluorosilane to the Cu-MOF@fibrous composite nanoparticles is 1:1-2:1; and the hydrolysis condensation reaction time is 2-4 hours.
[0009] (3) Preparation of photothermal super-hydrophobic coating dispersion: First, a low thermal conductivity binder is dissolved in an organic solvent, and then a non-solvent is added dropwise under stirring at room temperature to cause non-solvent-induced phase separation. Then, the low surface energy Cu-MOF@fibrous composite nanoparticles prepared in (2) are added, and the mixture is stirred for 2-4 hours and ultrasonicated for 20-40 minutes to form a low thermal conductivity binder / low surface energy Cu-MOF@fibrous composite nanoparticle microaggregate dispersion (photothermal super-hydrophobic coating dispersion); The low thermal conductivity binder is at least one of terminal hydroxyl polybutadiene and terminal hydroxyl polyisoprene; the mass fraction of the low thermal conductivity binder in the reaction system is 5% to 15%.
[0010] The organic solvent is at least one of methyl acetate, ethyl acetate, dimethyl carbonate, and butyl acetate; the non-solvent is at least one of methanol, ethanol, and isopropanol; the mass ratio of the solvent to the non-solvent is 1:1 to 3:1. The mass fraction of the low surface energy Cu-MOF@fibrous composite nanoparticles in the reaction system is 6% to 10%.
[0011] (4) Preparation of photothermal super-hydrophobic coating: Add curing agent isophorone diisocyanate and catalyst dibutyltin dilaurate to the dispersion prepared in (3) in sequence, stir for 8-12 minutes, and then spray it onto the substrate. Curing at room temperature for 70-75 hours can obtain a low thermal conductivity photothermal super-hydrophobic coating with a three-level micro / nano / nano structure.
[0012] The mass ratio of the curing agent isophorone diisocyanate to the low thermal conductivity binder is 1:9-1:11, and the mass ratio of the catalyst dibutyltin dilaurate to the low thermal conductivity binder is 1:90-1:110. The substrate includes aluminum alloy, magnesium alloy, glass, stainless steel, PP, and ABS.
[0013] SEM images of photothermal super hydrophobic coatings Figure 1 . From the low-magnification SEM, it can be observed that the coating has an obvious micro / nano hierarchical structure, which is mainly due to the phase separation of the low thermal conductivity binder to form microparticles and the low surface energy Cu-MOF@fibrous composite nanoparticles wrapped on its surface. Under high-magnification SEM, the coating shows a two-level nano / nano structure composed of Cu-MOF nanoparticles and fibrous clay mineral nanoparticles. Therefore, the coating has a three-level micro / nano / nano structure.
[0014] The present invention first grows photothermal Cu-MOF nanoparticles in situ on the surface of low thermal conductivity fibrous clay mineral nanoparticles, constructs a two-level nano / nano structure composite photothermal particle, then performs low surface energy modification and introduces a low thermal conductivity binder, and induces the binder to phase separate to form a micron-scale binder / low surface energy nanoparticle aggregate by non-solvent, and finally constructs a photothermal super-hydrophobic coating with a three-level micro / nano / nano structure by spraying. The three-level micro / nano / nano structure of the coating simultaneously gives the coating excellent photothermal performance under low temperature and high relative humidity environment and the Cassie-Baxter state stability of the droplet on the coating surface, so that it has excellent passive anti-icing / frosting and active deicing / defrosting performance in this environment. The low thermal conductivity of the coating further suppresses the heat exchange between the substrate and the water droplets, so that the passive anti-icing / frosting performance of the coating is further improved. In addition, the present invention also has the advantages of simple preparation method and large-scale preparation, which lays a solid foundation for the practical application of the photothermal super-hydrophobic anti-icing coating.
[0015] 2. Performance of Photothermal Super-Hydrophobic Coating (1) Superhydrophobic properties The coating prepared by the present invention has excellent super-hydrophobicity at room temperature, low temperature and high relative humidity environment: At room temperature, the contact angle (CA) of a 10 μL water droplet is >165°, and the sliding angle (SA) is <1°; the CA of a 1 μL water droplet is >160°, and the SA is <10° ( Figure 2); Under -10℃ and 80% relative humidity, the SA of a 10μL water droplet is <15° ( Figure 3 ); Under -20℃ and 80% relative humidity, the SA of a 10μL water droplet is <30° ( Figure 3 ).
[0016] (2) Photothermal performance The coating prepared by the present invention has excellent photothermal properties both at room temperature and at low temperature and in high relative humidity environments: At room temperature and 1 sun intensity, the temperature of the coating surface can rise to over 100°C within 8 minutes ( Figure 4 a); Under the conditions of -10℃, 80% relative humidity and 0.1 sun intensity, the temperature of the coating surface can rise to above 9℃ within 8 minutes ( Figure 4 b).
[0017] (3) Passive anti-icing performance The coating prepared by the present invention exhibits excellent static and dynamic passive anti-icing performance under low temperature and high relative humidity environment: Static passive anti-icing performance: Under -10℃ and 80% relative humidity, a 60μL water droplet did not freeze after 1 hour on the coating surface ( Figure 5 a); Also in this environment, the ice adhesion strength of the coating is <20kPa ( Figure 5 b); Under the environment of -10℃, 80% relative humidity and 0.1 sun intensity, a 60μL water droplet did not freeze after 5 hours on the coating surface.
[0018] Dynamic passive anti-icing performance: Under -10℃ and 80% relative humidity environment, 60μL supercooled water droplets continuously fall onto the coating surface (40-50 drops / min). After 2h, there is no ice accumulation on the coating surface.
[0019] (4) Passive anti-frost performance The passive anti-frost performance of the coating was studied by spraying cold water mist (0℃, 1.67g / min) with a humidifier in a -10℃ environment. The results showed that in this environment, after a 1h frost test, only a small amount of frost (~0.5mg / cm 2 )( Figure 5 c) Under the environment of -10℃ and 0.1 sun intensity, after 3h frosting test, no frost is formed on the surface of the coating.
[0020] (5) Active de-icing performance Under the conditions of -10℃, 80% relative humidity and 0.1 sun intensity, when the coating is tilted 15°, a 60μL frozen water droplet on its surface melts and rolls off within 3 minutes ( Figure 6 a); Under the same conditions, the ice on the coating surface (thickness 1mm) can melt and fall off within 45 minutes ( Figure 6 b).
[0021] (6) Active defrosting performance Under the conditions of -10℃, 80% relative humidity and 0.1 sun intensity, the frost (~1mm thick) on the coating surface melted within 10 minutes when the coating was tilted 15°. Figure 6 c).
[0022] In summary, compared with the prior art, the present invention has the following advantages: The design of the coating's low surface energy three-level micro / nano / nanostructure not only gives the coating excellent photothermal performance (room temperature, low temperature), but also greatly improves the stability of the Cassie-Baxter state of droplets on the coating surface in low temperature and high relative humidity environments, effectively improving the passive anti-icing / active deicing performance of the coating in low temperature and high relative humidity environments, and solving the defects of the practical application of traditional photothermal super-hydrophobic anti-icing coatings. In addition, through the synergistic effect of low thermal conductivity raw materials and extremely low solid-liquid contact area of super-hydrophobic coatings, the heat exchange between water droplets and the substrate is almost completely suppressed, further improving the passive anti-icing / frosting performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of the photothermal super-hydrophobic coating of the present invention.
[0024] Figure 2 a is the CA of 10 μL and 1 μL water droplets on the photothermal superhydrophobic coating of the present invention; Figure 2 b is the SA of 10 μL and 1 μL water droplets on the photothermal superhydrophobic coating of the present invention.
[0025] Figure 3 SA of 10 μL water droplets on the photothermal superhydrophobic coating of the present invention under low temperature and 80% relative humidity environment.
[0026] Figure 4 a is the change of temperature of the aluminum alloy and the surface of the photothermal super-hydrophobic coating of the present invention over time under room temperature and 1 sun illumination intensity environment; Figure 4 b is the change of temperature over time on the surface of the aluminum alloy and the photothermal super-hydrophobic coating of the present invention at -10°C, 80% relative humidity, and 0.1 sun intensity.
[0027] Figure 5a is the freezing time of a 60 μL water droplet on the surface of the aluminum alloy and the photothermal super-hydrophobic coating of the present invention under an environment of -10°C and 80% relative humidity; Figure 5 b is the adhesion strength of ice on the aluminum alloy and the surface of the photothermal super-hydrophobic coating of the present invention under an environment of -10°C and 80% relative humidity; Figure 5 c is the amount of frost accumulated on the surface of the aluminum alloy and the photothermal super-hydrophobic coating of the present invention after a 1-h frosting test at -10°C.
[0028] Figure 6 a is the deicing time of a 60 μL frozen water droplet on the surface of the aluminum alloy and the photothermal superhydrophobic coating of the present invention under an environment of -10°C, 80% relative humidity, and 0.1 sun intensity; Figure 6 b is the deicing time of a 1 mm ice layer on the surface of the aluminum alloy and the photothermal super-hydrophobic coating of the present invention under an environment of -10°C, 80% relative humidity, and 0.1 sun intensity; Figure 6 c is the defrosting time of a 1 mm frost layer on the surface of the aluminum alloy and the photothermal superhydrophobic coating of the present invention under an environment of -10°C, 80% relative humidity and 0.1 sun intensity. DETAILED DESCRIPTION
[0029] The preparation and performance of the photothermal super-hydrophobic coating of the present invention are further described below through specific examples.
[0030] Example 1 ① Dissolve 9.7g copper nitrate and 6.5g HHTP in 1L of N, N-dimethylformamide / water mixed solvent (v / v= 1 / 10), stir for 5min, then add 25g attapulgite nanoparticles, continue stirring at 85℃ for 15h (500rpm), then filter, wash, dry and grind the resulting suspension to obtain Cu-MOF@attapulgite composite nanoparticles with two-level nano / nano structure. ② Disperse 5g Cu-MOF@attapulgite composite nanoparticles in 440mL ethanol, stir for 10min and then ultrasonically disperse for 5min, then add 60mL ammonia water and stir for 5min, then add 7g perfluorodecyltriethoxysilane, react at room temperature for 2h, centrifuge, dry and grind the resulting suspension to obtain low surface energy Cu-MOF@attapulgite composite nanoparticles. ③ 7.5g of terminal hydroxyl polybutadiene binder was dissolved in 60g of butyl acetate, and then 29g of ethanol was added dropwise under stirring at room temperature to cause non-solvent induced phase separation to form terminal hydroxyl polybutadiene binder microaggregates, and then 7.9g of low surface energy Cu-MOF@attapulgite composite nanoparticles were added, stirred for 3h and assisted with ultrasonic dispersion for 30min to obtain a terminal hydroxyl polybutadiene binder / low surface energy Cu-MOF@attapulgite composite nanoparticle microaggregate dispersion. ④ 0.75g of isophorone diisocyanate and 0.075g of dibutyltin dilaurate were added to the terminal hydroxyl polybutadiene binder / low surface energy Cu-MOF@attapulgite composite nanoparticle microaggregate dispersion, stirred for 10min, and then sprayed onto an aluminum alloy substrate and cured at room temperature for 72h to obtain a low thermal conductivity photothermal superhydrophobic coating with a three-level micro / nano / nano structure. The coating properties are shown in Table 1.
[0031] Example 2 ① Dissolve 9.5g of copper nitrate and 6.9g of HHTP in 1L of a mixed solvent of N, N-dimethylformamide / water (v / v= 1 / 10), stir for 5min, then add 20g of halloysite nanoparticles, continue stirring at 85℃ for 15h (500rpm), then filter, wash, dry and grind the resulting suspension to obtain Cu-MOF@halloysite composite nanoparticles with a two-level nano / nano structure. ② Disperse 5.5g of Cu-MOF@halloysite composite nanoparticles in 460mL of ethanol, stir for 10min and then ultrasonically disperse for 5min, then add 40mL of ammonia water and stir for 5min, then add 8.4g of perfluorooctyltriethoxysilane, react at room temperature for 4h, centrifuge, dry and grind the resulting suspension to obtain low surface energy Cu-MOF@halloysite composite nanoparticles. ③ 6.8g of terminal hydroxyl polybutadiene binder was dissolved in 60g of dimethyl carbonate, and then 24g of ethanol was added dropwise under stirring at room temperature to cause non-solvent induced phase separation to form terminal hydroxyl polybutadiene binder microaggregates, and then 8.5g of low surface energy Cu-MOF@halloysite composite nanoparticles were added, stirred for 3h and assisted with ultrasonic dispersion for 30min to obtain a terminal hydroxyl polybutadiene binder / low surface energy Cu-MOF@halloysite composite nanoparticle microaggregate dispersion. ④ 0.7g of isophorone diisocyanate and 0.07g of dibutyltin dilaurate were added to the terminal hydroxyl polybutadiene binder / low surface energy Cu-MOF@halloysite composite nanoparticle microaggregate dispersion, stirred for 10min, and then sprayed onto the PP substrate and cured at room temperature for 72h to obtain a low thermal conductivity photothermal superhydrophobic coating with a three-level micro / nano / nano structure. The coating properties are shown in Table 2.
[0032] Example 3 ① Dissolve 9.1g copper nitrate and 6.2g HHTP in 1L of N, N-dimethylformamide / water mixed solvent (v / v= 1 / 10), stir for 5min, then add 28g sepiolite nanoparticles, continue stirring at 85℃ for 15h (500rpm), then filter, wash, dry and grind the resulting suspension to obtain Cu-MOF@sepiolite composite nanoparticles with two-level nano / nano structure. ② Disperse 5.6g Cu-MOF@sepiolite composite nanoparticles in 440mL ethanol, stir for 10min and then ultrasonically disperse for 5min, then add 60mL ammonia water and stir for 5min, then add 9.8g perfluorodecyltriethoxysilane, react at room temperature for 3h, centrifuge, dry and grind the resulting suspension to obtain low surface energy Cu-MOF@sepiolite composite nanoparticles. ③ 7g of terminal hydroxyl polybutadiene binder was dissolved in 60g of methyl acetate, and then 24g of ethanol was added dropwise under stirring at room temperature to cause non-solvent induced phase separation to form terminal hydroxyl polybutadiene binder microaggregates, and then 7.1g of low surface energy Cu-MOF@attapulgite composite nanoparticles were added, stirred for 3h and assisted ultrasonic dispersion for 30min to obtain terminal hydroxyl polybutadiene binder / low surface energy Cu-MOF@sepiolite composite nanoparticle microaggregate dispersion. ④ 0.7g of isophorone diisocyanate and 0.07g of dibutyltin dilaurate were added to the terminal hydroxyl polybutadiene binder / low surface energy Cu-MOF@sepiolite composite nanoparticle microaggregate dispersion, stirred for 10min, and then sprayed onto the ABS substrate and cured at room temperature for 72h to obtain a low thermal conductivity photothermal superhydrophobic coating with a three-level micro / nano / nano structure. The coating properties are shown in Table 3.
[0033] Example 4 ① Dissolve 9.7g copper nitrate and 6.5g HHTP in 1L of N, N-dimethylformamide / water mixed solvent (v / v= 1 / 10), stir for 5min, then add 25g attapulgite nanoparticles, continue stirring at 85℃ for 15h (500rpm), then filter, wash, dry and grind the resulting suspension to obtain Cu-MOF@attapulgite composite nanoparticles with two-level nano / nano structure. ② Disperse 5g Cu-MOF@attapulgite composite nanoparticles in 440mL ethanol, stir for 10min and then ultrasonically disperse for 5min, then add 60mL ammonia water and stir for 5min, then add 7g perfluorodecyltriethoxysilane, react at room temperature for 2h, centrifuge, dry and grind the resulting suspension to obtain low surface energy Cu-MOF@attapulgite composite nanoparticles. ③ 7.3g of terminal hydroxyl polyisoprene binder was dissolved in 60g of butyl acetate, and then 23g of ethanol was added dropwise under stirring at room temperature to cause non-solvent induced phase separation to form terminal hydroxyl polybutadiene binder microaggregates, and then 8.3g of low surface energy Cu-MOF@attapulgite composite nanoparticles were added, stirred for 3h and assisted with ultrasonic dispersion for 30min to obtain a terminal hydroxyl polyisoprene binder / low surface energy Cu-MOF@attapulgite composite nanoparticle microaggregate dispersion. ④ 0.73g of isophorone diisocyanate and 0.073g of dibutyltin dilaurate were added to the terminal hydroxyl polyisoprene binder / low surface energy Cu-MOF@attapulgite composite nanoparticle microaggregate dispersion, stirred for 10min, and then sprayed onto a glass substrate and cured at room temperature for 72h to obtain a low thermal conductivity photothermal superhydrophobic coating with a three-level micro / nano / nano structure. The coating properties are shown in Table 4.
Claims
1. A method for preparing a photothermal super-hydrophobic coating with excellent anti-icing / deicing performance under low temperature and high relative humidity environment, comprising the following process steps: (1) Preparation of Cu-MOF@fibrous composite nanoparticles: Dissolve copper nitrate and 2,3,6,7,10,11-hexahydroxytriphenylenebenzene in a mixed solvent of N,N-dimethylformamide / water, stir for 3-8 minutes, then add low thermal conductivity fibrous clay mineral nanoparticles, continue stirring at 80-90°C for 10-15 hours, filter the resulting suspension, wash, dry, and grind to obtain Cu-MOF@fibrous composite nanoparticles with a two-level nano / nano structure; (2) Preparation of low surface energy Cu-MOF@fibrous composite nanoparticles: The Cu-MOF@fibrous composite nanoparticles prepared in (1) were dispersed in ethanol, stirred for 8-12 minutes, and then ultrasonically dispersed for 4-6 minutes. Ammonia water was then added and stirred for 4-6 minutes. Then, fluorosilane was added. The fluorosilane was hydrolyzed and condensed on the surface of the Cu-MOF@fibrous composite nanoparticles at room temperature. Finally, the obtained suspension was centrifuged, dried, and crushed to obtain low surface energy Cu-MOF@fibrous composite nanoparticles. (3) Preparation of photothermal superhydrophobic coating dispersion: First, a low thermal conductivity binder is dissolved in an organic solvent, and then a non-solvent is added dropwise under stirring at room temperature to cause non-solvent-induced phase separation. Then, the low surface energy Cu-MOF@fibrous composite nanoparticles prepared in (2) are added, and the mixture is stirred for 2-4 hours and ultrasonicated for 20-40 minutes to form a low thermal conductivity binder / low surface energy Cu-MOF@fibrous composite nanoparticle microaggregate dispersion. (4) Preparation of photothermal super-hydrophobic coating: Add curing agent isophorone diisocyanate and catalyst dibutyltin dilaurate to the dispersion prepared in (3) in sequence, stir for 8-12 minutes, and then spray it onto the substrate. Curing at room temperature for 70-75 hours can obtain a low thermal conductivity photothermal super-hydrophobic coating with a three-level micro / nano / nano structure.
2. The method for preparing a photothermal super-hydrophobic coating having excellent anti-icing / deicing performance under a low temperature and high relative humidity environment as claimed in claim 1, characterized in that: In step (1), the concentration of the copper nitrate in the mixed solvent of N,N-dimethylformamide / water is 8-12 mg / mL; the concentration of the 2,3,6,7,10,11-hexahydroxytriphenylene benzene in the mixed solvent of N,N-dimethylformamide / water is 5-7 mg / mL; and in the mixed solvent of N,N-dimethylformamide / water, the volume ratio of N,N-dimethylformamide to water is 1:
10.
3. The method for preparing a photothermal super-hydrophobic coating having excellent anti-icing / deicing performance under a low temperature and high relative humidity environment as claimed in claim 1, characterized in that: In step (1), the low thermal conductivity fibrous clay mineral nanoparticles are one of attapulgite, halloysite, and sepiolite; and the concentration of the low thermal conductivity fibrous clay mineral nanoparticles in a mixed solvent of N,N-dimethylformamide / water is 15-40 mg / mL.
4. The method for preparing a photothermal super-hydrophobic coating having excellent anti-icing / deicing performance under a low temperature and high relative humidity environment as claimed in claim 1, characterized in that: In step (2), the volume ratio of ethanol to ammonia water is 49:1-40:10; the fluorosilane is one of perfluorooctyltriethoxysilane and perfluorodecyltriethoxysilane, and the mass ratio of fluorosilane to Cu-MOF@fibrous composite nanoparticles is 1:1-2:1; and the hydrolysis condensation reaction time is 2-4 hours.
5. The method for preparing a photothermal super-hydrophobic coating having excellent anti-icing / deicing performance under a low temperature and high relative humidity environment as claimed in claim 1, characterized in that: In step (3), the low thermal conductivity binder is at least one of terminal hydroxyl polybutadiene and terminal hydroxyl polyisoprene; and the mass fraction of the low thermal conductivity binder in the reaction system is 5% to 15%.
6. The method for preparing a photothermal super-hydrophobic coating having excellent anti-icing / deicing performance under a low temperature and high relative humidity environment as claimed in claim 1, characterized in that: In step (3), the organic solvent is at least one of methyl acetate, ethyl acetate, dimethyl carbonate, and butyl acetate; the non-solvent is at least one of methanol, ethanol, and isopropanol; and the mass ratio of the solvent to the non-solvent is 1:1 to 3:
1.
7. The method for preparing a photothermal super-hydrophobic coating having excellent anti-icing / deicing performance under a low temperature and high relative humidity environment as claimed in claim 1, characterized in that: In step (3), the mass fraction of the low surface energy Cu-MOF@fibrous composite nanoparticles in the reaction system is 6% to 10%.
8. The method for preparing a photothermal super-hydrophobic coating having excellent anti-icing / deicing performance under a low temperature and high relative humidity environment as claimed in claim 1, characterized in that: In step (4), the mass ratio of the curing agent isophorone diisocyanate to the low thermal conductivity binder is 1:9-1:11; the mass ratio of the catalyst dibutyltin dilaurate to the low thermal conductivity binder is 1:90-1:
110.
9. The method for preparing a photothermal super-hydrophobic coating having excellent anti-icing / deicing performance under a low temperature and high relative humidity environment as claimed in claim 1, characterized in that: In step (4), the substrate includes aluminum alloy, magnesium alloy, glass, stainless steel, PP, and ABS.
Citation Information
Patent Citations
Super-hydrophobic icing prevention coating with active photothermal deicing function, coating layer, preparation method of coating and application of coating
CN109486269A
A method for preparing a soft, elastic, superhydrophobic surface with low ice adhesion and photothermal effect
CN115260897B
Preparation method and application of two-component wear-resistant super-hydrophobic coating
CN113637401A
Preparation method and application of novel super-hydrophobic photo-thermal MOF (Metal Organic Framework)-based surface with ice removing / preventing functions
CN116515459A
Super-hydrophobic coating based on two-dimensional Cu-CAT-1 metal organic framework hierarchical structure and used for icing prevention and photo-thermal deicing and preparation method of super-hydrophobic coating
CN117736647A
Cited By
Photo-thermal super-hydrophobic coating based on waste powdered ink as well as preparation method and application of photo-thermal super-hydrophobic coating
CN120829722A
Silver paste electrode protection structure for flat plate excimer lamp and preparation method of silver paste electrode protection structure
CN122337945A
A silver paste electrode protection structure for a flat panel excimer lamp and a preparation method thereof
CN122337945B